Ludo Formation-a new lithostratigraphic unit in Quaternary of Central Algarve - Moura, Delminda (2013)
A new lithostratigraphic unit (Ludo Formation) is proposed aiming a more objective approach to mapping the Quaternary sedimentary series in the central Algarve.